KOMBINASI LA DAN FCO SEBAGAI PENGAMAN TRANSFORMATOR DISTRIBUSI DI PT. PLN (PERSERO) AREA BALI SELATAN - I Putu Adi Sumastra; I Gede Dyana Arjana; I Wayan Rinas (Program Studi Teknik Elektro UNUD, 2021)
The 20 Kv distribution network at Dewa Ruci has 61 distribution substations using the SUTMnetwork with AAAC conductors 1 x 150 mm², because distribution substations are placed in theopen, lightning surge disturbances and overloads that result in damaged transformers,transformers need protection against disturbances, so selected LA placement before and afterFCO to protect the transformer from lightning surge interference with a fast 4/10 us wavepropagation. Placement of LA before the FCO with a distance of 2 meters from the transformerthere is a voltage increase of 89.3515748 kV with a working voltage of LA 87 kV for a LAprotection factor of 95.7 kV, the possibility of LA failing to secure the transformer. Placement ofLA after FCO with a distance of 0.3 meters from the transformer there is a voltage increase of13.40273622 kV still at the working voltage and LA protection factor so that the transformer isstill safe.